Apolipoprotein E ε4 does not affect cognitive performance in patients with Parkinson's disease. (August 2016) - Mengel, David; Dams, Judith; Ziemek, Jannis; Becker, Julian; Balzer-Geldsetzer, Monika; Hilker, Rüdiger; Baudrexel, Simon; Kalbe, Elke; Schmidt, Nele; Witt, Karsten; Liepelt-Scarfone, Inga; Gräber, Susanne; et al.
Abstract: Introduction: Cognitive impairment is a common and disabling non-motor symptom in Parkinson's disease (PD). The apolipoprotein E (APOE) allele ε4 is a known risk factor for Alzheimer's disease and has also been suggested to be a risk factor for dementia in PD and even a predictor of impairment in certain cognitive domains. Methods: A total of 447 PD patients (PD patients without cognitive impairment: n = 187; PD patients with mild cognitive impairment: n = 188; PD patients with dementia: n = 72) were included from an ongoing observational German multicenter cohort study (LANDSCAPE study). All patients underwent an extensive neuropsychological test battery, including assessments of memory, visuospatial functioning, attention, language, and executive function. APOE genotype was determined by an allelic discrimination assay. Linear regression analysis was used to explore the associations between APOE-ε4 and cognitive performance. Results: The APOE-ε4 allele was not associated with a diagnosis of cognitive impairment in PD (PD with mild cognitive impairment and PD with dementia) or with deficits in specific neuropsychological domains in our study cohort. Conclusion: Our data question the relevance of the APOE-ε4 allele as a predictor of cognitive impairment in PD. Highlights: Cognitive impairment is a common and disabling symptom in PD. 447 PD patients were tested with an extensive neuropsychological test battery. The APOE status was determined. APOE-ε4 was not associated with PD-MCI/PDD or deficits in any neuropsychological domain.